Risk analysis for GB rail: today and tomorrow. Issue 3 (2nd July 2016) - Dacre, Marcus; Harrison, Chris; Hunt, Matt
Abstract: This chapter describes how data and risk analysis support safety-related decision making on Britain's mainline railway. It describes ongoing work to redevelop the industry's Safety Management Information System and explores opportunities for improving safety monitoring and risk modelling by extracting intelligence from new sources of data. Some of the challenges associated with the use of larger and more varied data sets in risk analysis are also discussed.